The influence of K-wire transfixation on proximalization of the first metacarpal after resection suspension interposition arthroplasty - Fritz, Niklas; Ludolph, Ingo; Arkudas, Andreas; Horch, Raymund E.; Cai, Aijia (Archives of Orthopaedic and Trauma Surgery, 2021)
Introduction: Osteoarthritis of the first carpometacarpal joint is a common degenerative disease and surgical treatment includes resection suspension interposition arthroplasty (RSIA) with or without temporary transfixation of the first metacarpal. One major drawback includes proximalization of the first metacarpal during the postoperative course. Specific data comparing different transfixation techniques in this context is sparse. Materials and methods: In this retrospective study, we measured the trapezial space ratio (TSR) in 53 hands before and after RSIA to determine the proximalization of the first metacarpal depending on the type of Kirschner (K)-wire transfixation. We, therefore, compared transfixation of the first metacarpal to the scaphoid with one K-wire (1K) to transfixation of the first metacarpal with two K-wires (2K), either to the carpus (2Ka), or to the second metacarpal (2Kb), or to both second metacarpal and carpus (2Kc). Results: While preoperative TSR did not differ between group 1K and 2K (p = 0.507), postoperative TSR was significantly higher in group 2K compared to 1K (p = 0.003). Comparing subgroups, postoperative TSR was significantly higher in group 2Kc than 1K (p = 0.046), while we found no significant difference comparing either group 2Ka or 2Kb to 1K (p = 0.098; p = 0.159). Neither did we find a significant difference within 2K subgroups, comparing group 2Ka and 2Kb (p = 0.834), 2Ka and 2Kc (p = 0.615), or 2Kb and 2Kc (p = 0.555). Conclusions: The results of our study suggest that transfixation with two K-wires should be preferred to transfixation with one K-wire after RSIA. Specifically, transfixation from first to second metacarpal and from first metacarpal to carpus resulted in least proximalization of the first metacarpal postoperatively.
CRIS-Team Scopus Importer:2021-02-05
Keywords: CMC1 joint; First metacarpal proximalization; K-wire transfixation; Osteoarthritis; Resection suspension arthroplasty; Saddle joint